Communication in organizations and 360-degree evaluation: what is the relationship between the two concepts? - Mourão, R. A. (2017)
The performance appraisal has a very important role in the strategic objectives of the organization, because it contributes to its efficacy (Aguinis, 2007). However, some limitations of top-down performance appraisal like the subjectivity have been proposed other evaluations, like 360-degree evaluation (Kondrasuk, 2012). This is a specific evaluation that considers more than one appraiser (Brutus & Gorriti, 2005). The purpose of this research is to know if the application of 360-degree evaluation influences organizational communication. We conducted a qualitative exploratory study through the interviews with experts. The results that will be presented are still preliminary and have theoretical and practical applications. In general, we conclude that 360-degree evaluation could be advantageous for organizational communication (e.g. active voice of employees; symmetrical and bi-directional communication).